Constelante x/y/z Spatial Direction Project: Aggregator of Light and Darkness Three-Dimensional Mapping Without The Use of Artificial Satélites - Borges, Valdecir de Godoy (Advances in Social Sciences Research Journal, 2024)
Ψ - Light and Darkness (L/D) Spatial Positioner, based on light perturbation. N - Velocity Input. Z - Spatial Graph.